Evaluation and Repair of Bridge Truss Gusset Plates - Hill, Howard; Mcgormley, Jonathan C.; Lewis, Jonathan; Clarke, Wade; Nagle, Thomas (Engineering Journal, 2014)
Gusset plates used to connect members in large steel trusses are important elements in many existing bridge structures. As such, their capacities can influence bridge structural load ratings, especially when the effects of deterioration and/or damage have become significant. In order to provide accurate load ratings, avoid unnecessary repairs and, when necessary, design appropriate repairs, gusset plate conditions and characteristics must be properly incorporated in the responsible engineer's evaluation. Because the cost of being conservative is far greater for existing structures than for new designs, engineers evaluating existing gusset plates should not rely too heavily on design-based methods when making final load rating and repair decisions. The purpose of this paper is to provide some practical guidance to the process of gusset plate evaluation and repair in order to promote efficient use of limited bridge maintenance resources.